2015
DOI: 10.1080/21645515.2015.1021522
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of a large mumps outbreak: Clinical severity, complications and association with vaccination status of mumps outbreak cases

Abstract: In recent years, large mumps outbreaks, involving mainly adolescents and young adults, have re-emerged in several countries. We investigated a large mumps outbreak, evaluated the association between mumps clinical severity (complications, hospitalization) and vaccination status (number of previous measles, mumps and rubella -MMR vaccine doses), and assessed vaccine effectiveness. The first mumps cases emerged in an ultra-orthodox boys' school in Jerusalem and were epidemiologically linked to the mumps outbreak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
32
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 19 publications
5
32
0
3
Order By: Relevance
“…12 The clinical findings of fever with parotid gland swelling was similar to a study conducted by Zamir et al where parotid gland swelling was found in 94.4% of cases and fever was found in 55% of cases. 13 The same findings were also found in a study conducted by Martina et al 14 The average duration of parotid gland swelling was 8 days in present study and this finding was comparable to a study conducted by Indranil et al where mean duration of swelling was 6.91±1.95 days. 8 The study findings with respect to complications like orchitis and meningitis are comparable to a study conducted by Zamir et al and Yung et al 13,15 …”
supporting
confidence: 82%
“…12 The clinical findings of fever with parotid gland swelling was similar to a study conducted by Zamir et al where parotid gland swelling was found in 94.4% of cases and fever was found in 55% of cases. 13 The same findings were also found in a study conducted by Martina et al 14 The average duration of parotid gland swelling was 8 days in present study and this finding was comparable to a study conducted by Indranil et al where mean duration of swelling was 6.91±1.95 days. 8 The study findings with respect to complications like orchitis and meningitis are comparable to a study conducted by Zamir et al and Yung et al 13,15 …”
supporting
confidence: 82%
“…However, mumps outbreaks have occurred in the United States in the last decade, including the large outbreak centered around a university in Iowa, which had over 5,000 cases in 2006 [3639]. Mumps outbreaks have also been reported in vaccinated populations in Europe and Asia [2023,40,41]. None of these outbreaks were associated with a genotype A MuV, which was the Jeryl Lynn vaccine genotype.…”
Section: Discussionmentioning
confidence: 99%
“…Le nombre de complications signalées en lien avec cette éclosion d'oreillons était faible, ce qui pourrait traduire des lacunes dans la surveillance de la santé publique, car l'étude des cas pourrait avoir été effectuée avant que les complications se manifestent. Il est possible que la vaccination précédente contre les oreillons ait conféré une certaine protection contre les maladies graves (21,22). Étant donné que les complications étaient rarement signalées, il n'a pas été possible d'analyser l'efficacité du vaccin contre les complications graves liées aux oreillons.…”
Section: Résultats De Laboratoireunclassified